Long-term outcomes of extending dual antiplatelet therapy after drug-eluting stent implantation for acute coronary syndrome: a large single-center study - Jingjing Xu; Ying Song; Zhan Gao; Ping Jiang; Ru Liu; Huanhuan Wang; Shubin Qiao; Runlin Gao; Yuejin Yang; Bo Xu; Jinqing Yuan (Platelets, 2020)
To date, DAPT duration of 1 year is the standard treatment for ACS patients after DES implantation in China. However, less is known about the effect of prolonging DAPT duration of long-term outcome for this kind of patient in the real world of China. We carried out a large sample case in the biggest cardiovascular center in China to observe the effect of prolonging DAPT duration for more than 1 year on long-term outcome in ACS patients after PCI. We enrolled 5187 consecutive patients with ACS who underwent DES implantation from January 2013 to December 2013. We recorded when DAPT was discontinued, and analyzed patients’ data comparing different DAPT durations (DAPT = 1 year or >1 year). Two-year clinical outcomes were compared between patients from the two groups. The baseline characteristics were almost the same between the two groups, except the number of stents per patient (DAPT = 1 year vs. >1 year, 1.80 ± 1.02 vs. 1.86 ± 1.05, p = .04). Patients with DAPT = 1 year had a higher incidence of all-cause death (1.8% vs. 0.1%, p < .01), cardiac death (0.8% vs. 0.1%, p < .01), and stent thrombosis (0.7% vs. 0.2%, p < .01) vs. DAPT > 1 year, respectively. Logistic regression analysis indicated that the number of stents per patient was an independent factor for prolonged DAPT (odds ratio: 1.07, 95% confidence interval (CI): 1.01–1.14, p = .03). Cox regression analysis showed that the independent risk predictors of all-cause death were age and cardiac dysfunction, whereas the independent protective predictors were body mass index and DAPT > 1 year. In the subgroup analysis of high bleeding risk, the DAPT > 1-year group still experienced a lower incidence of all-cause death. For patients with ACS undergoing DES implantation, 1 year of DAPT may be not sufficient. Appropriate prolongation of DAPT may relate to the reduction of the incidence of adverse cardiovascular events and it does not increase the bleeding events, even for the patients with high bleeding risk.